2020
DOI: 10.7150/thno.51287
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed dual-plasmonic gold nanorod@cuprous selenide hybrid heterostructures by regioselective overgrowth for in vivo photothermal tumor ablation in the second near-infrared biowindow

Abstract: NIR-II plasmonic materials offer multiple functionalities for in vivo biomedical applications, such as photothermal tumor ablation, surface-enhanced Raman scattering biosensing, photoacoustic imaging, and drug carriers. However, integration of noble metals and plasmonic semiconductors is greatly challenging because of the large lattice-mismatch. This study reports the regioselective overgrowth of Cu 2-x Se on gold nanorods (GNRs) for preparation of dual-plasmonic G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Noble metal nanoparticles (NPs), such as Au, Pd, and Pt, have attracted extensive attention in the therapeutic field owing to their tunable localized surface plasmon resonance (LSPR) characteristics, good biocompatibility, strong NIR light absorption and enzyme-like activity across the visible and near-infrared spectral range. [23][24][25][26][27][28] It was well known that the incident light on plasmonic metal nanoparticles could excite localized surface plasmon resonance (LSPR), which leads to strong enhancement of the electromagnetic field and energetic charge carrier generation. 29,30 Importantly, the generated energetic charges can promote the reactive oxygen species (ROS) generation by both chemical and energy transformation process, and release the heat through non-radiative transition process, attaching the plasmonic nanostructures with the photodynamic and photothermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Noble metal nanoparticles (NPs), such as Au, Pd, and Pt, have attracted extensive attention in the therapeutic field owing to their tunable localized surface plasmon resonance (LSPR) characteristics, good biocompatibility, strong NIR light absorption and enzyme-like activity across the visible and near-infrared spectral range. [23][24][25][26][27][28] It was well known that the incident light on plasmonic metal nanoparticles could excite localized surface plasmon resonance (LSPR), which leads to strong enhancement of the electromagnetic field and energetic charge carrier generation. 29,30 Importantly, the generated energetic charges can promote the reactive oxygen species (ROS) generation by both chemical and energy transformation process, and release the heat through non-radiative transition process, attaching the plasmonic nanostructures with the photodynamic and photothermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic Au NRs have been proven as good photothermal converters through Landau damping, hot electron generation, and heat dissipation to environment. [ 38–41 ] According to Chang's theoretical calculation and experimental demonstration, [ 29 ] Bi 2 Se 3 /CdSe semiconductor heterojunction with type‐II band alignment could effectively separate electrons and holes in spatial and then inhabitate raiative recombination of photo‐excited carriers, promoting heat generation. When a Bi 2 Se 3 /CdSe heterojunction is placed at the plasmonic hotspots of Au NRs, plasmon‐induced local field enhancement can enhance its absorption and photo‐excited electron‐hole pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the PTCE of both AuNCs and AP3-AuNCs was higher than gold nanorods (GNRs) and organic nanoparticle under the 808 nm-laser. This illustrated that AP3-AuNCs can facilitate the photothermal ablation of cancer cells [ 32 , 33 ]. Further, AP3 drug release from AP3-AuNCs can be further triggered and promoted by using 808 nm laser irradiation at 1 W/cm 2 .…”
Section: Resultsmentioning
confidence: 99%